Process for preparation of labisia pumila extract - M. M., Yusoff; Wan Nazimoon, Wan Mohamud (2011)
A process for the preparation of Labisia pumila extract from Labisia pumila plant material and to obtain an optimized and reproducible chemical profile by high performance liquid chromatography.